Waist Circumference Might Be a Predictor of Primary Liver Cancer: A Population-Based Cohort Study - Wei, Luopei; Li, Ni; Wang, Gang; Feng, Xiaoshuang; Lyu, Zhangyan; Li, Xin; Wen, Yan; Chen, Yuheng; Chen, Hongda; Chen, Shuohua; Wu, Shouling; Dai, Min; et al. (Frontiers in Oncology, 2018)
Background: Waist circumference, as an indicator of central adiposity, has been identified as an important predictor of several specific cancers such as colorectal cancer and gastroesophageal cancer risk, however, a consensus regarding the association between waist circumference and primary liver cancer (PLC) risk has not been reached. Methods: A total of 104,825 males participating in the health checkup were included in the Kailuan male cohort study (2006-2015). Information on demographic and socioeconomic characteristics, lifestyle, medical records and anthropometric measures were collected. Restricted cubic spline (RCS) and Cox proportional hazards regression models were used to estimate the hazard ratio (HR) and 95% confidence interval (CI) of association between waist circumference and the risk of PLC in males. Results: During a median of 8.9 years of follow-up, 346 PLC cases were newly diagnosed in the cohort. The RCS model showed a U-shaped association between waist circumference and PLC risk (P-overall=0.019, P-non-linear = 0.017). Overally, males with both high waist circumference (HRQ5vs.Q3=1.98, 95%CI: 1.39-2.82) and low waist circumference (HRQ1vs.Q3=1.52, 95%CI: 1.02-2.27) had an increased risk of PLC. Especially, the U-shaped association between waist circumference and PLC risk tended to be strengthened among subjects with hepatitis B surface antigen (HBsAg) negativity (HRQ5vs.Q3 =2.39, 95%CI: 1.43-3.98; HRQ1vs.Q3=2.27, 95%CI=1.29-4.01). Conclusions: Waist circumference might be an independent predictor of PLC risk in males, especially for subjects with HBsAg negativity. Controlling waist circumference in an appropriate range might be an effective primary prevention to decrease PLC risk.